A Neurodisparity Index of Nationwide Access to Neurological Health Care in Northern Ireland - McCarron, Mark O.; Clarke, Mike; Burns, Paul; McCormick, Michael; McCarron, Peter; Forbes, Raeburn B.; McCarron, Luke V.; Mullan, Fiona; McVerry, Ferghal (Frontiers in Neurology, 2021)
Nationwide disparities in managing neurological patients have rarely been reported. We compared neurological health care between the population who reside in a Health and Social Care Trust with a tertiary neuroscience centre and those living in the four non-tertiary centre Trusts in Northern Ireland. Using the tertiary centre Trust population as reference, neurodisparity indices (NDIs) were calculated from residency status in each Trust per 100,000 population for four neurological pathways - intravenous thrombolysis (iv-tPA) and mechanical thrombectomy (MT) for acute ischaemic stroke (AIS), disease modifying treatment (DMT) in multiple sclerosis (MS) and admissions to a tertiary neurology ward. Neurological management was recorded in 3026 patients. Patients resident in the tertiary centre Trust were more likely to receive AIS treatments (iv-tPA and MT) and access to the neurology ward (p<0.001) than patients residing in other Trusts. DMT use for patients with MS was higher in two non-tertiary centre Trusts than in the tertiary centre Trust. There was a geographical gradient for MT for AIS patients and ward admissions. Averaged NDIs for non-tertiary centre Trusts were: 0.48 (95%CI 0.32-0.71) for patient admissions to the tertiary neurology ward, 0.51 (95%CI 0.34-0.76) for MT in AIS patients, 0.78 (95%CI 0.67-0.92) for iv-tPA in AIS patients, and 1.11 (95%CI 0.99-1.26) for DMT use in MS patients. There are important neurodisparities in Northern Ireland, particularly for MT and tertiary ward admissions. Neurologists and health service planners should be aware that geography and time-dependent management of neurological patients worsen neurodisparities.